Saltmarsh plants, but not fertilizer, facilitate invertebrate recolonization after an oil spill. Issue 1 (18th January 2018) - Johnson, David Samuel; Fleeger, John W.; Riggio, Maria Rita; Mendelssohn, Irving A.; Lin, Qianxin; Graham, Sean A.; Deis, Donald R.; Hou, Aixin
Abstract: Foundation species contribute to the recovery of animal communities from disturbance by engineering, by improving habitat quality, and by regulating food availability. In a salt marsh impacted by the Deepwater Horizon oil spill, we tested the hypothesis that nutrient subsidies would enhance the positive effects of the foundation species Spartina alterniflora on the initial recolonization of benthic invertebrate communities (e.g., copepods, annelids, nematodes) by augmenting food (i.e., microalgae) availability. After two months, plantings of S. alterniflora significantly elevated the densities of the polychaete Capitella capitata, meiofauna‐sized annelids, and total macroinfauna over unplanted plots. After 7 months, the significant effect of plantings persisted for meiofauna‐sized annelids, but not for C. capitata and total macroinfauna. Plantings had no effect on copepods (including Nannopus palustris, the dominant species), nematodes, or microalgal biomass for either month. Nutrient additions did not influence any taxon, despite initial increases in benthic microalgal biomass after 2 months. We hypothesize that the structural effects of plants were important to early colonization, possibly by facilitating larval settlement or ameliorating temperature and desiccation stress. Our results emphasize the importance of re‐establishing foundation species in oil‐impacted sites to enhance recolonization of saltmarsh annelids, but suggest that recolonization is not promoted by the addition of nutrients.